CHANGES IN THE TAX SYSTEM OF THE TOURISM IN THE EUROPEAN UNION COUNTRIES IN TIME OF THE WORLD PANDEMIC - Mudra , Y.A. (The actual problems of regional economy development, 2020)
The article is aimed on studying the mechanisms of tax policy of the European Union (the EU) with a focus on approaches to taxation of the tourism business before and during 2020. The need for research is changes in tax and financial legislation in the EU under the influence of the global pandemic COVID-19. The main aspects of taxation and approaches is to the implementation of tax policy in the EU countries with the highest criterion of tourist attractiveness and the number of visits. Statistics are presented, which show the degree of employment in the tourism business and the impact of tourism business on EU GDP growth in general and in individual countries in particular. The percentage of tax payments with the levels of government is shown, which proves the need to support tourism as an important business unit for employment in the tourism sector and maintain the attractiveness of tourist countries and locations for the growth of domestic and foreign tourist flows. The financial and tax mechanisms and instruments are introduced by individual EU countries to support enterprises that have suffered losses under quarantine conditions and limit their activities during the global pandemic are analyzed. Emphasis is placed on changes in the general EU policy on the provision of tax information by member states on residents and non-residents in the business environment and tourism in particular.